PERANCANGAN IKLAN AUDIO VISUAL “YOESANI SHOES” - MHD KAELANI IKHSAN, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this audio-visual ad selection is to generate an effective and efficient promotion design in accordance with the advantages of audio-visual advertising, which can reach broad goals. In addition, with this audio visual ads later than as a media campaign is also expected to introduce